Identity Development and Future Orientation in Immigrant Adolescents and Young Adults: A Narrative View of Cultural Transitions From Ethiopia to Israel. Issue 160 (6th April 2018) - Flum, Hanoch; Buzukashvili, Tamara
Abstract: This paper examines a major aspect of identity development in the context of cultural transition. Following Eriksonian psychosocial and sociocultural perspectives, it investigates self‐continuity and identity integration in light of inherent discontinuity among young immigrants. More specifically, this examination draws on three distinct narrative studies, within the framework of Dynamic Narrative Approach, with first‐ and second‐generation adolescents and young adult Ethiopian immigrants to Israel. Their negotiations of identity, with a focus on their narrative construction of past, present, and future across life domains (education, career, military service, family), are illustrated in this article in a variety of developmental paths. Dynamics of reciprocity between early life experiences and future orientation are revealed in the narratives. A capacity to connect cultural resources in the past with challenges in the new culture is identified as a key. By processing them and bringing them up‐to‐date, meaning becomes relevant to current experiences and developmental challenges. Across the three distinct studies, a variety of exploratory activities and relational qualities are found to facilitate or impede the reconstruction and integration of identity.